AN ANALYSIS OF GENDER AND STATUS AFFECTING CONVERSATIONAL INTERRUPTIONS - Sapabsri, Orapan; Dhanesschaiyakupta, Ubon; Ackrapong, Tipa Thep; Phimswat, On Usa (PEOPLE: International Journal of Social Sciences, 2018)
Interruptions as conversational strategies can be used to achieve either dominance or cooperation in a talk. The purpose of this study was to analyze conversational interruptions between Thai genders with different social statuses. Five episodes of the talk show BeMyGuest sponsored by the Thai Government’s Department of Public Relations were selected to analyze which type of interruption, intrusive or cooperative, males with different social statuses made in interacting with the woman show host. A total of 217 utterances were analyzed for interruptions under Zimmerman and West’s (1975) guidelines. The results revealed that in the context of the woman having a higher or equal status as a man, the male interrupted the conversation more often than his conversation partner. However, in the case the host having a lower social status than the male guest, it was found that the woman interrupted more often than the man. The result in the last case does not support the dominance approach, which points out that men dominate women in conversation. Culture is considered an important factor accounting for the genders’ behavior of interruptions in the conversation.